Kolaborasi Sekolah Bersinar dan Guru PAI dalam Menanamakan Nilai-Nilai Pendidikan Karakter untuk Pencegahan Penyalahgunaan Narkoba pada Siswa SMA Negeri 14 Bone - Erfidah; Yahya, Muhammad; Wahyuni, Sri (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the collaboration between BERSINAR schools and Islamic Religious Education (PAI) teachers in instilling character education values to prevent drug abuse in students at SMA Negeri 14 Bone. This study used a qualitative approach with an exploratory research design. Data were obtained by interviewing PAI teachers and students at SMA Negeri 14 Bone. The results showed that the PAI teachers carried out their role in instilling character values through three main roles: as teachers by linking teaching materials to Islamic teachings and the dangers of drugs, using varied methods, and instilling religious values, discipline, and responsibility in students' learning and habits. As role models, teachers demonstrated religious attitudes, discipline, and responsibility that reflected real examples for students in staying away from drugs. As motivators, teachers provided moral and spiritual guidance to raise students' awareness in protecting themselves from drugs. The contribution of PAI teachers has been proven to be able to shape religious, disciplined, and responsible characters as a whole, which serve as a strong foundation in fortifying students from drug abuse and contributing to the creation of a healthy and drug-free school environment, in line with the predicate of SMA Negeri 14 Bone as a BERSINAR School (Drug-Free).